LEGAL PROTECTION OF CIVILIANS DURING THE IRAN-ISRAEL CONFLICT ACCORDING TO THE 1949 JANEVAL CONVENTION - Anandika Abrar Tamba; Muhammad Nasir Sitompul (Inspiring Law Journal, 2025)
International law is law that applies to all countries globally. Civilians in any armed conflict are guaranteed international legal protection, as armed conflict falls within the scope of international law. The international legal provisions governing the protection of civilians are contained in the 1949 Geneva Convention.            This study discusses the legal protection of civilians in the midst of the armed conflict between Iran and Israel. The research method used in this study is normative juridical with a statutory approach, combining library research with an examination of official regulations directly related to the legal issues and problems faced by civilians during armed conflict.            The research results indicate that both countries committed serious violations and are suspected of violating the 1949 Geneva Conventions and are liable for such violations. This research is expected to enrich the literature on international law, particularly regarding humanitarian law and the protection of civilians during armed conflict.